Plantation forestry: what the future holds - Kamis Awang (2014)
Plantation forestry is an important strategy in overcoming the shortage of wood supply from the natural forests. However, its future development is linked to a number of issues that need to be addressed. These are related to sustainable forest development, wood supply-demand scenario, public versus private sector involvement, market prospects and utilisation potential, investment incentives, land and labour, species selection, and research and training. These issues are discussed.